An effective method for evaluating thermal parameters of diode-based thermal sensors. (May 2020) - Liu, Chao; Fu, Jianyu; Hou, Ying; Liu, Ruiwen; Zhou, Qiong; Chen, Dapeng
Graphical abstract: Highlight: An electrical method is proposed to measure thermal parameters by self-heating effect. The theory and technique to accurately extract thermal parameters is analyzed. The validity is verified by an IR FPA and consistent with the theoretical analysis. Abstract: Diode-based thermal sensors have a wide range of applications in industry and civil. Thermal conductance, heat capacity and thermal time constant are three main thermal parameters of diode-based thermal sensors. Extracting their thermal parameters is of great importance in evaluating sensors' performance. In this work, an effective electrical circuit is developed to determine these thermal parameters of diode-based thermal sensors. The method takes advantage of self-heating effect of sensors and involves the measurement of time dependent forward voltage drop of sensors under a square-pulse voltage. The technique to accurately extract thermal parameters from the circuit is analyzed carefully, and its validity is verified experimentally using an infrared focal plane array with series diodes. The experimental results are in good agreement with the theoretical analyses of structure. The measurement technology is very easy for engineers to grasp.